Compromises between Occupational Aspirations and VET Occupations—a Contribution to the Reproduction of Social Inequalities? - Schels, Brigitte; Kleinert, Corinna; Fischer-Browne, Melanie; Ahrens, Lea (Zeitschrift für Soziologie, 2022)

Compromises in occupational choice and premature termination of vocational education and training: gender type, prestige, and occupational interests in focus - Fischer-Browne, Melanie; Ahrens, Lea; Kleinert, Corinna; Schels, Brigitte (Empirical Research in Vocational Education and Training, 2024)
This study examines whether premature termination of vocational education and training (VET) is more likely when trainees have to make compromises between their realistic occupational aspirations and the occupation for which they are trained in terms of the occupational dimensions of gender type, prestige, and occupational interests. Specifically, it examines the relative importance of the three compromise dimensions on premature VET termination. The study is based on a sample of 3,241 VET entrants from a cohort of ninth graders in 2010 in the German National Educational Panel Study (NEPS-SC4) in combination with aggregated data on occupational characteristics. Results from discrete hazard rate models indicate a higher risk of premature VET termination for trainees whose VET occupation differs from their realistic occupational aspiration from their school days. While compromises in prestige have no overall effect, both compromises in interests and gender type threaten the stability of VET. The results also indicate that compromises in interests have the strongest effect on the risk of premature VET termination and that the effects of compromises in gender type are partly mediated by the effects of compromises in interests. Furthermore, sensitivity analysis revealed that the main effects of compromises in gender type and prestige are gender specific.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Gender type; Germany; Occupational compromising; Occupational interests; Premature termination of vocational training; Prestige

Compromises in Occupational Choice and Stability of Vocational Education and Training - Ahrens, Lea; Fischer, Melanie; Kleinert, Corinna; Schels, Brigitte (Pathways in Vocational Education and Training and Lifelong Learning. Proceedings of the 4th Crossing Boundaries Conference in Vocational Education and Training, 2021)

Nicht alle Wünsche werden wahr: Welche Kompromisse Jugendliche beim Ausbildungsberuf eingehen - Ahrens, Lea; Fischer, Melanie; Schels, Brigitte; Kleinert, Corinna (2021)

Not all wishes come true: the occupational compromises youths accept when entering vocational training - Ahrens, Lea; Fischer-Browne, Melanie; Kleinert, Corinna; Schels, Brigitte (2021)

Pushing Higher or Lower? Divergent Parental Expectations and Compromises in Occupational Choice - Fischer-Browne, Melanie (Social Inclusion, 2022)
Many adolescents in Germany are unable to realize their realistic occupational aspirations when they transition from school to vocational education and training (VET). However, little is known about the underlying circumstances and what the compromises look like when these adolescents come to take up a VET occupation. As parents perform an important socialization role, which is also influential in occupational orientation, this article examines the role of divergent parental expectations. Are parental expectations, which differ from adolescents’ realistic occupational aspirations, related to the probability that adolescents will take up different occupations than they originally aspired to? Are relatively higher or lower parental expectations associated with a corresponding direction of compromise formation? Are there differences between men and women in the relationship between divergent parental expectations and compromise formation? This empirical analysis is based on a sample of 1243 VET entrants from the starting cohort 4 of the National Educational Panel Study (NEPS). The compromise formation of the adolescents is measured by comparing their realistic occupational aspirations from ninth grade with their first VET occupation. Results from multinomial logistic regression models show that adolescents adjust their occupational choices to their parents’ divergent expectations. Women are more likely to make compromises that accommodate their parents’ higher expectations.
CRIS-Team Scopus Importer:2022-06-17
Keywords: occupational aspirations; occupational choice; parental expectations; school‐to‐work transition

Soziale Disparitäten am Übergang in Sekundarstufe II und die Bedeutung der Distanz zur nächstgelegenen weiterführenden Schule - Fischer, Melanie; Zeichner, Christina; Hoffmann, Johannes (Bildungsentscheidungen und lokales Angebot. Die Bedeutung der Infrastruktur für Bildungsentscheidungen im Lebensverlauf., 2018)
Bei Betrachtung von Bildungsentscheidungen steht in der Sozialforschung insbesondere die Erklärung sozialer Ungleichheiten an den Übergängen von der Primar- in die Sekundarstufe I sowie von der Sekundarstufe II in den tertiären Bildungssektor im Fokus. Während sich die Forschungslage bezüglich des Übergangsgeschehens am Ende der Sekundarstufe I zwar deutlich lückenhafter gestaltet, ist diese jedoch nicht minder wichtig für den weiteren Lebenslauf. Denn auch zu diesem Zeitpunkt stehen Jugendliche vor der Entscheidung, wie sie ihren weiteren Bildungsverlauf gestalten. Der Beitrag beschäftigt sich deshalb mit der Erklärung sozialer Disparitäten bei der Bildungsentscheidung, nach Abschluss der Sekundarstufe I die Schullaufbahn an einer weiterführenden Schule fortzusetzen oder in eine Berufsausbildung überzugehen. Ein besonderes Augenmerk liegt dabei auf der Bedeutung der Entfernung zur nächstgelegenen weiterführenden Schule. Auf Basis rationaler Handlungstheorien (Boudon, 1974; Breen & Goldthorpe, 1997; Esser, 1999) wird postuliert, dass diese Determinante als Kostenfaktor insbesondere von Schülerinnen und Schülern niedriger sozialer Herkunft im Entscheidungsprozess berücksichtigt wird. Die Datengrundlage für das Forschungsvorhaben umfasst die Daten der Bevölkerungsbefragungen des Projektes „BildungsLandschaft Oberfranken (BiLO)“. Die Analysen beziehen sich auf eine Teilstichprobe von 246 Schülerinnen und Schülern, die im Herbst 2015 zu Beginn ihres Abschlussschuljahres erstmals sowie im darauffolgenden Herbst 2016 im Nachgang ihres Übergangs interviewt wurden. Während erste deskriptive Ergebnisse die Grundannahmen sozialer Disparitäten im Bildungserwerb sowie regionaler Disparitäten im Zugang zu Bildungseinrichtungen stützen, belegen multivariate Schätzungen darüber hinaus, dass räumliche Gelegenheitsstrukturen im Zuge der Bildungsentscheidung insbesondere für Schülerinnen und Schüler niedriger sozialer Herkunft relevant sind.<br

Studienortwahl - räumliche Entfernungen im Fokus - Fischer, Melanie; Baur, Hanna-Rieke (Bildungsentscheidungen und regionales Angebot. Die Bedeutung der Infrastruktur für Bildungsentscheidungen im Lebensverlauf., 2018)
Steht die räumliche Entfernung zu Hochschulen in Zusammenhang mit der Studienentscheidung? Wie wichtig ist Studienberechtigten die Wohnortnähe des Studienortes und unterscheidet sich dies nach sozialer Herkunft? Der vorliegende Beitrag betrachtet die Wahl des Studienortes als einen Teilaspekt der Studienentscheidung, bei dem insbesondere Ungleichheiten sichtbar werden können, die sich aus der räumlichen Verortung von Wohn- und Studienort ergeben. Die Studienortwahl wird als rationaler Auswahlprozess verstanden, im Zuge dessen junge Erwachsene über einen längeren Zeitraum hinweg verschiedene Studienorte in Betracht ziehen, Vor- und Nachteile der Alternativen gegeneinander abwägen und so infrage kommende Hochschulen sequenziell bis hin zur endgültigen Wahl ausschließen. Ob die Entfernung zwischen Wohn- und Studienort als materieller oder auch immaterieller Kostenfaktor im Rahmen des Auswahlprozesses einschränkend wirkt, wird auf Individualebene anhand via Georeferenzierung gewonnener Distanzen zu potenziellen Studienorten untersucht. Auf Basis deskriptiver Auswertungen zeigt sich, dass im Auswahlprozess zunehmend wohnortnahe Studienorte infrage kommen. Gleichzeitig werden dabei soziale Disparitäten sichtbar: Studienberechtigte niedrigerer sozialer Herkunft ziehen über den Auswahlprozess hinweg tendenziell näher gelegene Studienorte in Betracht als Studienberechtigte höherer sozialer Herkunft.<br